2022
DOI: 10.1186/s40813-022-00251-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of influenza A virus prevalence and transmission dynamics in backyard swine populations globally

Abstract: Background Backyard swine farming is critical to generating subsistence and food security in rural and peri-urban households in several developing countries. The objective of this systematic review was to analyze the molecular and serological prevalence of influenza A virus (IAV) in backyard swine populations globally. Results We identified 34 full-text research articles in NCBI-PubMed and Google Scholar databases that have reported IAV sero- and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Most cases of Mpox in animals were detected in nonhuman primates and rodents; only one study each reported Mpox DNA in a pet dog ( Canis lupus familiaris ) [ 154 ] and antibodies in a domestic pig ( Sus scrofa domesticus ) [ 113 ]. While domestic pigs are reported to harbor several virus pathogens, including RNA [ 186 , 187 , 188 , 189 , 190 , 191 , 192 ] and DNA [ 193 , 194 ] viruses, the occurrence of Mpox antibodies in a domestic pig indicates the possibility of natural infection of domestic pigs with Mpox and warrants the surveillance of Mpox in domestic pig populations to investigate their status and significance.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of Mpox in animals were detected in nonhuman primates and rodents; only one study each reported Mpox DNA in a pet dog ( Canis lupus familiaris ) [ 154 ] and antibodies in a domestic pig ( Sus scrofa domesticus ) [ 113 ]. While domestic pigs are reported to harbor several virus pathogens, including RNA [ 186 , 187 , 188 , 189 , 190 , 191 , 192 ] and DNA [ 193 , 194 ] viruses, the occurrence of Mpox antibodies in a domestic pig indicates the possibility of natural infection of domestic pigs with Mpox and warrants the surveillance of Mpox in domestic pig populations to investigate their status and significance.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of sampling on farms, additional information on farms was also reviewed (herd size, pig density, and accommodation types) ( 9 ). If the variables were not found in the literature, they were marked as “not reported.” An adequate sample size to estimate the pooled prevalence and seroprevalence was calculated to achieve the desired precision of 95% confidence intervals (CIs) using previously reported data and methodology (at least 600 and 750 samples were required for prevalence and seroprevalence, respectively) ( 18 20 ). Attempts were made to contact the authors for further information related to their study if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…The influenza virus belongs to the Orthomyxoviridae family and includes four genera, Alphainfluenzavirus, Betainfluenzavirus, Gammainfluenzavirus, and Deltainfluenzavirus, corresponding to influenza virus A (IAV), B (IBV), C (ICV), and D (IDV), respectively [71]. IAV has a broad host spectrum and is one of the most critical causative pathogens of viral respiratory diseases in avians, humans, and pigs [72][73][74]. In addition, it can spill over from avians to humans and pigs, causing rapid spread and evolution of the virus between and within species [74][75][76].…”
Section: Influenza a Virusmentioning
confidence: 99%
“…IAV has a broad host spectrum and is one of the most critical causative pathogens of viral respiratory diseases in avians, humans, and pigs [72][73][74]. In addition, it can spill over from avians to humans and pigs, causing rapid spread and evolution of the virus between and within species [74][75][76]. The surface antigen haemagglutinin (HA) is subdivided into 18 HA subtypes (H1-H18) [73].…”
Section: Influenza a Virusmentioning
confidence: 99%